Penerapan Vector Error Correction Model pada Hubungan Kurs, Inflasi dan Suku Bunga: (The Implementation of the Vector Error Correction Model on Foreign Exchange, Inflation and Interest Rates) - Moh Faizin (UPT Penerbitan Universitas Jember, 2021)
The stable condition and absence of a country is reflected in the stability of the currency exchange rate and with respect to the rate of inflation and benchmark interest rates. The aim of the study analyzes short-term and long-term relationships between exchange rate variables, inflation and interest rates in Indonesia. The study uses the VECM data secondary time series mode l for the period 2011-2019. Results show that short-term relationships occur only on inflation variables affecting the exchange rate, while others are not significant. Results also show that out of all three rate variables, inflation and interest rates there is a long-term reciprocal relationship.